The river of silver : tales from the Daevabad trilogy - Chakraborty, S. A. (Harper Voyager, an imprint of HarperCollinsPublishers, 2022)
Told from the perspective of characters both beloved and hated, this new compilation of stories set in Daevabad enrich a world already teeming with magic and wonder, inviting readers to explore this kingdom hidden from human eyes.